2019
DOI: 10.2166/ws.2019.123
|View full text |Cite
|
Sign up to set email alerts
|

Surface runoff and pollutant load response to urbanization, climate variability, and low impact developments – a case study

Abstract: Using the Storm Water Management Model (SWMM), this study evaluated the impacts of (a) 20% and 50% urbanization at the mountainous Mahabad Dam watershed in Iran, as probable future land developments, (b) the urbanization location (near the outlet, in the middle, and at the far end of the watershed), (c) climate variability (increase in evaporation and rainfall intensity), and (d) implementing vegetative swales as low impact developments (LIDs), on watershed-generated runoff and pollutant loads (total suspended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Jamali et al showed that lack of adaptation to climate variations leads to a considerable decrease in efficiency in Iran's Karkheh Hydropower in the future [51]. Some examples of a lack of insufficient climate assessment studies and improper managements in Iran are: damages caused by heavy rains; floods and damages on many houses, infrastructure, water and power supply; groundwater depletion; droughts and their impacts on food quality and quantity, economy, health, and people's livelihood; drying lakes; sand storms; and ecosystem degradation [52][53][54][55][56][57][58][59][60][61][62]. These issues indicate the necessity of implementing sustainable adaptation and mitigation plans, considering possible variations in climate.…”
Section: Resultsmentioning
confidence: 99%
“…Jamali et al showed that lack of adaptation to climate variations leads to a considerable decrease in efficiency in Iran's Karkheh Hydropower in the future [51]. Some examples of a lack of insufficient climate assessment studies and improper managements in Iran are: damages caused by heavy rains; floods and damages on many houses, infrastructure, water and power supply; groundwater depletion; droughts and their impacts on food quality and quantity, economy, health, and people's livelihood; drying lakes; sand storms; and ecosystem degradation [52][53][54][55][56][57][58][59][60][61][62]. These issues indicate the necessity of implementing sustainable adaptation and mitigation plans, considering possible variations in climate.…”
Section: Resultsmentioning
confidence: 99%
“…Land use is identified as a vital factor affecting the runoff generation, soil erosion and nitrogen and phosphorus loads in a watershed [21,45]. Forests have a great ability to intercept precipitation and increase infiltration, because of their mature canopy, rich litter humus layer and complex root system [46].…”
Section: Discussionmentioning
confidence: 99%
“…The computational predictions are based on mathematical modelling. The mathematical models can be of assistance in obtaining a reasonably accurate representation of the water quality across the system, which can later be verified or confirmed through limited sampling (Jalal 2008;Nazari-Sharabian et al 2019a, 2019b. The hydraulic models mainly consider advection and decay while calculating the water quality in the water distribution system.…”
Section: Water Qualitymentioning
confidence: 99%